Nonlocal problem with integral conditions for a high-order hyperbolic equation - Yusubov, Sh. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the solvability of a nonlocal problem with integral conditions for a high-order hyperbolic equation withpredominant mixed derivative. The posed problem is reduced to the integral equation and the existence of its solutionis proved by the help of a priori estimates.